2012
DOI: 10.1007/s11356-012-1133-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Remazol Black B adsorption onto carbon prepared from sugar beet pulp

Abstract: Dried sugar beet pulp, an agricultural solid waste, was used for the production of carbon. Carbonised beet pulp was tested in the adsorption of Remazol Black B dye, and adsorption studies with real textile wastewater were also performed. Batch kinetic studies showed that an equilibrium time of 180 min was needed for the adsorption. The maximum dye adsorption capacity was obtained as 80.0 mg g(-1) at the temperature of 25 °C at pH = 1.0. The Langmuir and Freundlich adsorption models were used for the mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Finally, Table 2 presents the maximum adsorption capacities of RB and NR of several adsorbents reported in literature [7,17,[40][41][42][43]. Those materials were selected based on their composition.…”
Section: Modelmentioning
confidence: 99%
“…Finally, Table 2 presents the maximum adsorption capacities of RB and NR of several adsorbents reported in literature [7,17,[40][41][42][43]. Those materials were selected based on their composition.…”
Section: Modelmentioning
confidence: 99%
“…Therefore, various abundance, renewability, cost-effectiveness and ecofriendly materials have been attracting interests of researchers. In recent years, agricultural wastes have been employed to prepare AC, such as the sugar beet pulp (Dursun et al 2013;Ma et al 2014) and corn wastes (Abdel-Ghani et al 2015). From the literature, it is clear that the starting material significantly influences physical and chemical properties of AC and adsorption property as a result.…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet pulp has a respectable content of cellulose, hemicellulose and lignin, which was suitable for preparation of AC. To our knowledge, some researchers have used sugar beet pulp as starting material to prepare AC and investigated their adsorption properties (Ozer and Tumen 2003;Samadi et al 2009;Demiral and Gündüzoglu 2010;Dursun et al 2013), and few literatures focused on the separation of dyes, but only for heavy metal removal.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic analysis for the dye adsorption of AC was carried on almost all the studies. Dursun et al (2013) did batch kinetic studies on the adsorption of Remazol Black B dye with dried sugar beet pulp. The results indicated that both external mass transfer and intraparticle diffusion were important in the adsorption mechanisms of dye.…”
Section: Ficus Carica Fiber Based Activated Carbon (Fcac)mentioning
confidence: 99%